Early Development of the Gut Microbiota and Immune Health - M. Pilar Francino (Pathogens, 2014)
In recent years, the increase in human microbiome research brought about by the rapidly evolving “omic” technologies has established that the balance among the microbial groups present in the human gut, and their multipronged interactions with the host, are crucial for health. On the other hand, epidemiological and experimental support has also grown for the ‘early programming hypothesis’, according to which factors that act in utero and early in life program the risks for adverse health outcomes later on. The microbiota of the gut develops during infancy, in close interaction with immune development, and with extensive variability across individuals. It follows that the specific process of gut colonization and the microbe-host interactions established in an individual during this period have the potential to represent main determinants of life-long propensity to immune disease. Although much remains to be learnt on the progression of events by which the gut microbiota becomes established and initiates its intimate relationships with the host, and on the long-term repercussions of this process, recent works have advanced significatively in this direction.